BRICOLAGE Y PARODIA EN LA CULTURA DE LA CONVERGENCIA - Dr. Javier MORAL MARTÍN, (Fonseca, Journal of Communication, 2023)
In Convergence culture, collaborative practices have been commonly understood as exercises located between the amateur and the professional. This characterization involves an implicit underestimation of amateurism because, in a single organization hierarchy, is considered as a preliminary step to the professional world and, therefore, a more imperfect activity.